Application of Vitis vinifera Microcapsules on Cotton Fabric: A Potential to Prevent UV-Induced Skin Problems - Deepti Pargai; Shahnaz Jahan (Journal of Natural Fibers, 2020)
Considering the harmful effect of UV radiation, present study was aimed at developing a UV protective finish for cotton fabric using Vitis vinifera leaves extract. Process parameters of the study were optimized for getting maximum UV protection while maintaining other physical properties of the fabric. Box and Behnken design was used under response surface methodology (RSM) for optimization process. It was found that 3.574% concentration of microcapsules with 2.942% concentration of binder at 120.664°C curing temperature were selected as optimum conditions for application of Vitis vinifera microcapsules on cotton fabric. It can be concluded that application of Vitis vinifera microcapsules on cotton fabric incorporates UV protection properties on cotton fabric, which can helpful to prevent various UV-induced skin problems.